2021
DOI: 10.3390/w13162242
|View full text |Cite
|
Sign up to set email alerts
|

Reclaimed Water for Vineyard Irrigation in a Mediterranean Context: Life Cycle Environmental Impacts, Life Cycle Costs, and Eco-Efficiency

Abstract: The agricultural sector in the Mediterranean region, is increasingly using reclaimed water as an additional source for irrigation. However, there is a limited number of case studies about product-based life cycle analysis to ensure that the overall benefits of reclaimed water do indeed outweigh the impacts. The Life Cycle Assessment (LCA) and Life Cycle Costing (LCC) methods are used in this study to investigate the environmental impacts and costs of vineyard cropping systems when tertiary reclaimed water is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 30 publications
0
15
0
1
Order By: Relevance
“…Similarly, LCA and eco-efficiency assessment have pointed to a similar direction that water reclamation for irrigation delivered economic and environmental benefits [10,46], although the results are likely site-specific [47]. An LCA study by Meneses et al (2010) [10] demonstrated that the agricultural use of reclaimed water from a WWTP located on the Mediterranean coast offers environmental and economic benefits, especially when compared to desalinated water, and that water reclamation should be encouraged when freshwater is scarce.…”
Section: Cost-benefit Analysis Of Water Reclamation Projects For the ...mentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, LCA and eco-efficiency assessment have pointed to a similar direction that water reclamation for irrigation delivered economic and environmental benefits [10,46], although the results are likely site-specific [47]. An LCA study by Meneses et al (2010) [10] demonstrated that the agricultural use of reclaimed water from a WWTP located on the Mediterranean coast offers environmental and economic benefits, especially when compared to desalinated water, and that water reclamation should be encouraged when freshwater is scarce.…”
Section: Cost-benefit Analysis Of Water Reclamation Projects For the ...mentioning
confidence: 97%
“…An LCA study by Meneses et al (2010) [10] demonstrated that the agricultural use of reclaimed water from a WWTP located on the Mediterranean coast offers environmental and economic benefits, especially when compared to desalinated water, and that water reclamation should be encouraged when freshwater is scarce. Based on an eco-efficiency assessment, Canaj et al (2021) [46] suggested that reclaimed water could be used to generate an economically profitable yield of vineyard cultivation in Acquaviva Delle Fonti, Italy while also offering net environmental benefits.…”
Section: Cost-benefit Analysis Of Water Reclamation Projects For the ...mentioning
confidence: 99%
“…Similarly, the results of LCA conducted by Romeiko (2019) indicated that replacing groundwater with reclaimed water as the irrigation source significantly decreased life cycle global warming, acidification, ozone depletion, smog formation, and respiratory impacts of corn, soybean, and wheat systems in Northern China. The LCA conducted by Canaj et al (2021) further revealed that tertiary reclaimed water as a supplementary source of irrigation water could reduce the net environmental impact by 23.8% due to lower consumption of irrigation water (À50%), electricity (À27.7%), and chemical fertilizers (À22.6%) compared with conventional groundwater irrigation system in Italy.…”
Section: Life Cycle Assessment Of the Wrrf Contribution To Uamentioning
confidence: 99%
“…The average gross irrigation requirement was 5000 m 3 /ha. The key inventory data for table grape production [10] was retrieved from the Cooperative Society of Agricultural Producers "La Molignana" in Acquaviva delle Fonti (40 • 55 37.1 N; 16 • 50 47.8 E). The full-scale tertiary treatment was based on surface filtration (disk filters) and UV disinfection to treat an equalized average flow rate of 6720 m 3 /day, equal to about 280 m 3 /h.…”
Section: Inventory Datamentioning
confidence: 99%
“…Other studies [9] report LCC by describing the economic burden of the product life cycle, alongside its environmental impacts. Recently, Canaj et al [10] provided a quantitative assessment of the environmental impacts, costs, and eco-efficiency of crop production with reclaimed water.…”
Section: Introductionmentioning
confidence: 99%